1994
DOI: 10.1128/jcm.32.4.1130-1131.1994
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas species exhibit aggregative adherence to HEp-2 cells

Abstract: Clinical and environmental isolates ofAeromonas species (five A. hydrophila isolates, three A. caviae isolates, and two A. sobria isolates) were tested for their adherence to HEp-2 cells. Clinical isolates ofA. hydrophila and A. sobria exhibited aggregative adherence similar to that presented by enteroadherent-aggregative Escherichia coli. Bacterial aggregates adhered to cells with a typical "stacked-brick" appearance. In contrast, A. caviae strains showed a diffuse adherence pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 9 publications
2
11
1
Order By: Relevance
“…hydrophila and Aer. veronii biovar sobria (Neves et al 1994). The LogA and LA patterns found in our study have not been previously reported for Aeromonas.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…hydrophila and Aer. veronii biovar sobria (Neves et al 1994). The LogA and LA patterns found in our study have not been previously reported for Aeromonas.…”
Section: Discussioncontrasting
confidence: 55%
“…hydrophila isolates from clinical (Guimarães et al 2002) and seafood (Scoglio et al 2001) sources, suggesting that this adhesion pattern may be common to this species worldwide. Similarly, the AggA pattern has also been reported in both clinical (Neves et al 1994) and seafood isolates (Scoglio et al 2001) of Aer. caviae and in clinical isolates of Aer.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The majority (67%) of the A. caviae strains tested presented an aggregative adherence pattern to Caco-2 cells, in accordance with the previous study. Diffuse and aggregative adherence patterns were observed for A. hydrophila as reported by Guimarães et al (2002) and Neves et al (1994) for Caco-2 and to HEp-2 cells, respectively.…”
Section: Discussionsupporting
confidence: 54%
“…hydrophila can enter into a VBNC state when grown in nutrient-poor conditions. As also referred by other authors (Neves et al 1994;Thornley et al 1996), the tested Aer. hydrophila strain exhibited an aggregative adherence pattern.…”
Section: Discussionsupporting
confidence: 53%